CHEMICAL COMPOSITION OF CERTAIN SYNTHETIC DRUGS USED IN KIDNEY AND URINARY BLADDER DISEASES (Scientific journal of the Fergana State University, 2023)
Information about chemical composition of Torasemidum, Uralyt-U, 5-NOK, Arimidex, Nitroxoline-50, Ciprinol and other synthetic drugs used to treat the kidney and the urinary bladder ailments were given in this article.Furthermore, it is recommended that orderly consuming natural, food additives such as Shifoi bosim, Nishifo, Asdavo, Askalsiy, Antivir 101 instead of synthetic drugs that to treat kidney and bladder system disesases is effective.